2016
DOI: 10.1007/s40368-016-0230-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes regarding molar incisor hypomineralisation amongst Saudi Arabian dental practitioners and dental students

Abstract: MIH is a condition encountered by Saudi dentists who advocated the need for clinical training regarding MIH-aetiological and therapeutic fields. Students have little exposure to MIH and are likely to have similar concerns upon commencement of dental practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
60
3
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(95 citation statements)
references
References 14 publications
27
60
3
5
Order By: Relevance
“…In general, and as in other studies 8,[15][16][17][18]21 , dentists' responses re ect the hypothesis that the etiology may be multifactorial, with a diversity of responses. Most studies, when describing etiological factors, attribute MIH primarily to "chronic and acute medical conditioners affecting the mother and child" 8,15,16,19 .…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…In general, and as in other studies 8,[15][16][17][18]21 , dentists' responses re ect the hypothesis that the etiology may be multifactorial, with a diversity of responses. Most studies, when describing etiological factors, attribute MIH primarily to "chronic and acute medical conditioners affecting the mother and child" 8,15,16,19 .…”
Section: Discussionsupporting
confidence: 72%
“…We found that PDs had twice the perception of patients with MIH lesions compared with GDPs, a situation re ected in countries such as Iraq 15 , Malaysia 22 , Australia-New Zealand 18 , Saudi Arabia 17 , China 8 and the UK 20 , where the prevalence of MIH is similar to Spain. Both in Spain and in other countries 15,17,18 , the general perception of dentists is that there is an increase in the incidence of MIH, although in our case the perception is signi cantly higher in PDs than in GDPs. Thus, 59.45% of GDPs responded that the prevalence of MIH patients is < 10%.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…However, there is also the potential to complete in-home applications of CPP-ACP products in an attempt to achieve remineralization, which could result in the lesser need of extensive treatment and fewer sensitivity complaints. Significantly, in a recent survey 40 carried out across dental students and dentists located in Riyadh, Saudi Arabia, a lack of insight into the management and overall diagnosis of MIH cases was found, with approximately 60% of the study sample stating they were unaware of a defect named MIH. When considering the notably high prevalence of MIH in the current investigation, there is a recognised need for continuing education courses in this regard-particularly encompassing both the diagnosis and the management of MIH and MH cases.…”
Section: Discussionmentioning
confidence: 97%